SUSTAINABLE DEVELOPMENT IN THE CONTEXT OF EDUCATION: SWEDISH REALITIES AND RUSSIAN POTENTIAL - Nina Alexeeva; Nikolay Kasimov; Yuri Mazurov; Sven-Erik Österlund; Alla Pakina; Andrius Plepys (Geography, Environment, Sustainability, 2011)
The goal of this paper is to discuss current problems of education for sustainable development, i.e. a global educational innovation that is actively growing in the new century. In Sweden, which has extensive experience in ecological education, education for sustainable development is considered a national model for the creation of the foundation for SD. In Russia, difficulties exist in defining and achieving SD objectives. It has been demonstrated that cooperation between Russia and Sweden in the field of ESD may prove to be very successful. Such cooperation is based on historical, cultural, and geographical factors. Examples of successful cooperation are joint educational projects aimed at improving the ESD framework and its practical implementation. The results of joint projects between the two countries have been analyzed in the context of mutual interests of Russia and Sweden and new goals for cooperation have been outlines.